Acute-on-Chronic Lithium Toxicity: A Simulation Case for Emergency Medicine Residents - Alyssa Thomas; Catherine M. Wares; Kathryn T. Kopec; Mark J. Bullard (Association of American Medical Colleges, 2023)
Introduction Simulation-based education has become standard within emergency medicine training. Toxicological clinical presentations are challenging to identify and treat in the emergency department. Recognizing that active teaching methods are superior to standard lecture for learner retention, we created an experiential simulation case for education on lithium toxicity. The case was written after an extensive literature review followed by consultation with a medical toxicologist and an expert in simulation-based education. Methods Fifty-three residents participated in a simulation scenario involving a lithium-poisoned patient over the course of eight simulation sessions. The scenario ran approximately 10 minutes and was followed by postevent debriefing. Debriefing was facilitated by an emergency medicine attending with specialized training in simulation-based education. Following the completion of the scenario, residents received an anonymous educational quality improvement survey assessing residents' perception of their ability to recognize and manage lithium toxicity as well as their comfort level with the lithium-poisoned patient. Results After the simulation, residents reported an increased comfort level with managing lithium-poisoned patients. Residents also self-reported an increased ability to recognize the signs and symptoms of lithium toxicity. Additionally, residents cited the case's educational importance and a desire to include this specific scenario in future simulation sessions. Discussion Compared to other disease processes, toxicological overdoses are infrequently seen in the emergency department. Health care simulation can effectively portray lithium toxicity for emergency medicine resident education in a safe, controlled environment to increase repetitive practice in caring for this challenging population.